INFORMATION AND COMMUNICATION TECHNOLOGY AS A CATALYST FOR HANDICRAFT BUSINESS SUCCESS IN DELHI/NCR - Nandi, Archita; Singh, D. P. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research investigates how the adoption of Information and Communication Technology (ICT) has influenced the marketing and sales of handicrafts in the Delhi/National Capital Region in the post-virus environment. Previous studies have highlighted the significant challenges faced by the handicraft sector due to reduced physical marketplaces and changing consumer behaviors during health crises, emphasizing the critical role of digital platforms such as e-commerce sites and social media in sustaining business operations. Building on these insights, this study employs a cross-sectional design with data collected from 234 artisans and enterprises using a standardized questionnaire. The focus is on understanding how the use of ICT tools—including digital marketing strategies, social media engagement, and online sales platforms—impacts sales performance. Analytical methods including reliability testing, descriptive statistics, and multiple regression analysis were applied to the data. The results demonstrate a strong positive relationship between ICT utilization and sales success, confirming that digital channels are vital for recovery and growth in the handicrafts industry post-virus. These findings provide valuable guidance for artisans, marketers, and policymakers on leveraging ICT effectively to enhance market reach and improve income, thereby supporting the resilience and advancement of traditional craft enterprises.